1996
DOI: 10.3109/10739689609148300
|View full text |Cite
|
Sign up to set email alerts
|

Control Mechanisms of Retinal Vein Pressure: Evaluation in the Cat Using an In Situ Infusion Micropipette

Abstract: Vein pressure in the cat retina is maintained above intraocular pressure by mechanisms other than active control. A passive high-resistance segment resides somewhere within the optic nerve possibly within the lamina cribosa or prelaminar region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It has been suggested that as IOP rises the accompanying mechanical responses of the tissues around the lamina cribrosa compress the vein, and outflow resistance is increased 1,5,9 . This theory is supported by the observations that variation in IOP causes movement of the optic disc 11 and lamina cribrosa, 12 and that reversal of cupping is seen following trabeculectomy 13,14 …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been suggested that as IOP rises the accompanying mechanical responses of the tissues around the lamina cribrosa compress the vein, and outflow resistance is increased 1,5,9 . This theory is supported by the observations that variation in IOP causes movement of the optic disc 11 and lamina cribrosa, 12 and that reversal of cupping is seen following trabeculectomy 13,14 …”
Section: Discussionmentioning
confidence: 93%
“…Increased IOP is accompanied by a reduction in ocular blood flow, 10 so outflow resistance must increase as IOP increases to allow retinal venous pressure to follow changes in IOP. Attariwala et al found no evidence for active venous responses to account for this relationship and concluded that outflow resistance changes passively in response to IOP changes 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation